The Influence of Work Ethic And Workload on Emplyee Performance (A Sensus on Dinas Koperasi, Usaha Mikro, Kecil dan Menengah, Perindustrian dan Perdagangan at Kota Tasikmalaya) - Dwiki Rizki Utama; Rita Tri Yusnita; Barin Barlian (Journal of Indonesian Management, 2023)
This purpose of this study to determine the effect of work ethic and workload on employee performance (census on Dinas Koperasi, Usaha Mikro, Kecil dan Menengah, Perindustrian dan Perdagangan at Kota Tasikmalaya). The method used is a quantitative method with a research sample of 58 respondents who are an employee at Dinas Koperasi, Usaha Mikro, Kecil dan Menengah, Perindustrian dan Perdagangan at Kota Tasikmalaya. The data is used primary data and secondary data. The analitytical tool in this research is multiple regression using by SPSS version 25. The result showed that simultaneously work ethic and workload has a significant influence on employee performance. Partially work ethic has a significant influence on employee performance. Partially workload has a significant on employee performance